The Microrna-143/145 Cluster in Tumors: A Matter of Where and When - Poli, Valeria (Cancers (Basel), 2020)
The establishment and spreading of cancer involve the acquirement of many biological functions including resistance to apoptosis, enhanced proliferation and the ability to invade the surrounding tissue, extravasate from the primary site, survive in circulating blood, and finally extravasate and colonize distant organs giving origin to metastatic lesions, the major cause of cancer deaths. Dramatic changes in the expression of protein coding genes due to altered transcription factors activity or to epigenetic modifications orchestrate these events, intertwining with a microRNA regulatory network that is often disrupted in cancer cells. microRNAs-143 and -145 represent puzzling players of this game, with apparently contradictory functions. They were at first classified as tumor suppressive due to their frequently reduced levels in tumors, correlating with cell survival, proliferation, and migration. More recently, pro-oncogenic roles of these microRNAs have been described, challenging their simplistic definition as merely tumor-suppressive. Here we review their known activities in tumors, whether oncogenic or onco-suppressive, and highlight how their expression and functions are strongly dependent on their complex regulation downstream and upstream of cytokines and growth factors, on the cell type of expression and on the specific tumor stage.